2014
DOI: 10.2478/eec-2014-0002
|View full text |Cite
|
Sign up to set email alerts
|

Women in Local Politics in Russia: Coping with Poverty and Strategies for Development

Abstract: In historical continuation from the Soviet Union, social policy is predominantly a female responsibility. e present article focuses on women in local politics, who have an important role in local change, and who; among others, cope with poverty and try to solve reasons and consequences of poverty. Based on interviews and observations, the article shows how women's entrepreneurial skills of handling various shortcomings in the Soviet system are re ected in their present strategies for social development in loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Changes in legal rules have also given rise to a responsibility for self-financing at the local level [4]. As women are responsible for social issues, this is also thought to increase their workload (Sätre, 2012(Sätre, , 2014c.…”
Section: A Theoretically Based Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in legal rules have also given rise to a responsibility for self-financing at the local level [4]. As women are responsible for social issues, this is also thought to increase their workload (Sätre, 2012(Sätre, , 2014c.…”
Section: A Theoretically Based Discussionmentioning
confidence: 99%
“…Although social policy partly continues to be financed by the state, it is organized in a new way. It is indicated that women who are responsible for social welfare have to find sponsors by themselves, for their regular activities (Sätre, 2014b(Sätre, , 2014c. Being responsible for organizing social welfare, women working in the social sphere have created their own support networks for this.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interviews also support the assumption that local authorities are able to mobilise the resources of local entrepreneurs for combatting poverty in Russia. This is about local politicians making use of their own human capital, as well as improving the skills of the local population through projects and educational programmes (see Sätre 2014c).…”
Section: Federal and Regional Programmesmentioning
confidence: 99%